1994
DOI: 10.1017/s0140525x00034361
|View full text |Cite
|
Sign up to set email alerts
|

A theory of visual stability across saccadic eye movements

Abstract: We identify two aspects of the problem of maintaining perceptual stability despite an observer's eye movements. The first, visual direction constancy, is the (egocentric) stability of apparent positions of objects in the visual world relative to the perceiver. The second, visual position constancy, is the (exocentric) stability of positions of objects relative to each other. We analyze the constancy of visual direction despite saccadic eye movements.Three information sources have been proposed to enable the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
150
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(155 citation statements)
references
References 177 publications
2
150
1
1
Order By: Relevance
“…In the present experiments, it has been shown that conceptionally this may be regarded as an extension of the calibration theory of Bridgeman et al (1994), enforced by the radial anisotropy of the visual field. Alternatively, it may be considered as a contextsensitive evaluation theory in the sense of MacKay (1973): the context is provided by the saccade target attended to immediately before the eyes start to move.…”
Section: -R------------mentioning
confidence: 59%
See 1 more Smart Citation
“…In the present experiments, it has been shown that conceptionally this may be regarded as an extension of the calibration theory of Bridgeman et al (1994), enforced by the radial anisotropy of the visual field. Alternatively, it may be considered as a contextsensitive evaluation theory in the sense of MacKay (1973): the context is provided by the saccade target attended to immediately before the eyes start to move.…”
Section: -R------------mentioning
confidence: 59%
“…One of the most recent suggestions for solving the problem of visual stability in the context of saccadic eye movements is the calibration solution of Bridgeman et al (1994). Basic to their approach is that it regards retinotopic representations as sufficient to ensure visual stability.…”
Section: -R------------mentioning
confidence: 99%
“…They suggest that most of the visual information before the saccade is discarded, and that a new representation of the visual world is generated from new incoming information after the saccade [73]. Only some information from the pre-saccadic image, particularly the position and properties of the saccade target, are encoded in trans-saccadic memory.…”
Section: Theories and Computational Models Of Peri-and Trans-saccadicmentioning
confidence: 99%
“…One compelling solution to this problem is that the visual system has the built-in assumption that the world as a whole does not change during an eye movement. A mechanism that becomes important here is saccadic suppression; indeed, it has been suggested that saccadic suppression 'bridges the errors' that remain due to the imperfect cancellation mechanism (Bridgeman et al, 1994). Therefore, let us next look at saccadic suppression.…”
Section: Space Constancy and The Role Of Efference Copies During Saccmentioning
confidence: 99%
“…Saccadic suppression of image displacement therefore seems to imply either that the required precise comparison is normally not performed, or that transsaccadic memory about the location of objects is not available to the visual system, or is very poor. Indeed, Bridgeman et al (1994) in their theoretical account of visual stability assumed that there is no need for transsaccadic memory of object positions, rather, the spatial positions are calculated anew after each saccade. This raises the question of the nature of transsaccadic memory, and of what and how much information is contained in this store.…”
Section: Saccadic Suppressionmentioning
confidence: 99%